2012
DOI: 10.1517/14712598.2012.685716
|View full text |Cite
|
Sign up to set email alerts
|

Plasma hTERT mRNA discriminates between clinically localized and locally advanced disease and is a predictor of recurrence in prostate cancer patients

Abstract: Plasma hTERT mRNA quantification can be both a useful non-invasive tumor marker for discriminating between localized and locally advanced PCa, as well as a prognostic factor of recurrence at the molecular level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 12 publications
0
18
0
1
Order By: Relevance
“…18,27,37 In the present study, rigorous efforts to eliminate DNA from samples of RNA, as well as limiting the number of cycles for amplification of hTERT cDNA to prevent false-positive results, might have contributed to diminished sensitivity. 18,27,37 In the present study, rigorous efforts to eliminate DNA from samples of RNA, as well as limiting the number of cycles for amplification of hTERT cDNA to prevent false-positive results, might have contributed to diminished sensitivity.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…18,27,37 In the present study, rigorous efforts to eliminate DNA from samples of RNA, as well as limiting the number of cycles for amplification of hTERT cDNA to prevent false-positive results, might have contributed to diminished sensitivity. 18,27,37 In the present study, rigorous efforts to eliminate DNA from samples of RNA, as well as limiting the number of cycles for amplification of hTERT cDNA to prevent false-positive results, might have contributed to diminished sensitivity.…”
Section: Discussionmentioning
confidence: 94%
“…18 In gastric cancer, 2 studies yielded very different results, namely 100% specificity and 8% sensitivity 36 versus 87% specificity and 66% sensitivity. This observation suggested highly specific diagnostic value (100% specificity), even though sensitivity was relatively low (22%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they found that serum hTERT mRNA level was significantly different in different tissues and could be used as a new and useful biomarker for cancer. March et al [18] also detected plasma hTERT mRNA content in 49 patients with prostate cancer and found plasma hTERT mRNA content was significantly higher in patients with locally advanced lesions than in patients with localized lesions. Thus, it can be used as a non-invasive marker of prostate cancer to differentiate patients with locally advanced disease at molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential clinical value of the detection of cfRNA in plasma did not attract the attention of researchers until 1999, when two parallel studies reported the detection of tyrosinase mRNA in patients with metastatic melanoma122 and mRNA associated with EBV in patients with nasopharyngeal carcinoma 123. Many studies have subsequently reported the presence of specific mRNA in plasma from patients with a variety of cancers including colon,124126 breast,127,128 prostate,129,130 melanoma,122 lung,131 and thyroid 132…”
Section: Circulating Cell-free Rna (Cfrna)mentioning
confidence: 99%